Estrategia didáctica "INTELECTUS" para mejorar el aprendizaje de solución de problemas en los estudiantes del tercer grado en el área de Ciencia, Tecnología y Ambiente de educación secundaria de la Institución Educativa Santa Isabel del distrito de nueva Cajamarca. - Vilcarromero Rojas, Leyda (2007)
The educative act is a complex process that occurs by means of the socialization, bough interactions of variables of the context. The family is basic the social group are the first interchanges of social and affective conducts take place, values and lefs, that they have a very decisive influence in the social behavior, in this case in front of the secularization process. Then the factors of the familiar surroundings secuence in the results of the educative process that develops the boy, for the sake of sir integral formation. In the educative institutions when one faces to analyze the results of the evaluation, we detected that there is in each group, a determined number of students / students who come obtaining a low academic yield. Analyzing the causes that can else it, we arrived at that they must in one or another measurement, to the mosphere partner-relative who surrounds to the boy or the girl. Fact that has activated to make an investigation whose objective was to determine the relation that it’s between the familiar context and the scholastic yield of the students of the level of binary Education in the located Educative lnstitutions in the Marginal Urban zone of district of Rioja in 2006. The investigation of the substantive type, of the descriptive level, with correlational insactional design, was carried out in the educative institutions located in the marginal in zone of the district of Rioja, considering the population sample of 342 students of first one to the sixth degree of level of the primary, registered and attending education in 2006. Of the test of chi square one took control the following relations: Between the rural level of the family and academic yield X2 (224,68) it is greater than x2; (21,03); been the interest of the family by the education and academic yield x2; (10,86) it is after than x2; (7,82); between the labor situation of the family and academic yield (162,74) it is greater than x2; (7,82); between the conjugal situation of the family academic yield. X2; (138,7) it is greater than x2; (7,82); between the bad treatments experiment the children in their houses and academic yield X2; ( 133, 185) are greater than x; (25), between status economic and academic yield x; (80,86) is greater than xl~ (12,59). From these relations the decision was to reject the null hypothesis and to accept he alternating one, consequently, affirms that direct relation between the familiar context and the academic yield of the students of the level of Primary Education in the located Educative lnstitutions in the Marginal Urban zone of the district of Rioja in 2006 exists.